Waste Management for Sustainable Tourism in the Hotel Industry - Muqtader, ZahraZaidi; Mahani, Mohammad Abdu Shakur; Urooj, Ahmed (2023)
The hospitality industry is a rapidly evolving and dynamic sector that operates around the clock as a vital part of the broader travel and tourism industry. This rapid expansion of the global tourism industry has brought forth the critical challenge of managing waste sustainably within the hotel sector. This research paper explores the interplay between waste management practices and sustainable tourism, utilizing a multi-case study approach to illuminate effective strategies employed by hotels. The study examines four diverse case studies - Hotel Verde, Kamalaya Koh Samui, Sandos Caracol Eco Resort, and Scandic Hotels - to uncover innovative waste reduction methods, policy influences, educational initiatives, and technological advancements. Through a rigorous analysis of these case studies, this research investigates the complex ecosystem of waste management practices and their broader implications on sustainable tourism outcomes. Findings reveal a range of waste management strategies, ranging from source segregation to circular economy principles, each contributing to reduced waste generation and enhanced resource conservation. The study also underscores the significant role of policies, collaborative efforts, and awareness campaigns in shaping responsible waste disposal behaviors among stakeholders. Moreover, emerging technologies such as smart waste bins and data analytics emerge as critical tools in optimizing waste collection processes. This research not only highlights the pressing need for effective waste management but also provides valuable insights for hotels seeking to integrate sustainability principles into their waste management practices. By underscoring the positive correlation between waste reduction and sustainable tourism, this study contributes to a more resilient and responsible future for the hospitality industry.